Shifting Boundaries: Community in a Blended e-Learning Experience - Terrie Lynn Thompson; Jennifer H. Kelland; Carmen G. Lawlor (Adult Education Research Conference, 2007)
This paper explores how learners construct and maintain community in a blended e-learning program in a graduate degree program. Findings suggest that individual’s expectations influenced their perceptions of the value of community, learners actively gauged how much of themselves to share, and feelings of community were enhanced by mixing face-to-face and online interactions.